Risk factors and prevention of needlestick instruments in the medical field - Alshammari, Fawaz Awdah Mohammad; Alshammari, Hassan Mohammed Brahim (International journal of health sciences, 2019)
Training is believed to be most effective when incorporated into healthcare workers' ongoing training regimen, allowing for new technologies to be showcased and for workers to be trained more than once since information retention decreases dramatically after a year. Cutting-edge ways of engaging healthcare workers are being developed to make the information easier to learn and maintain. In some simulations, scenarios can be used to demonstrate real-life situations. In the final analysis, developing properly trained healthcare workers is as important as legal mandates, especially if healthcare leadership is geared towards the novel one-stop shop approach. Workers themselves have stated the desire for employers to take the time and effort to keep them safe. Efficiently training healthcare workers to properly use needlestick preventative equipment is one of the most cost-effective means of reducing not only the risk but also the cost associated with needlestick injuries as well.